Rett syndrome: clinical review and genetic update - Weaving, L (BMJ Group, 2005)
Rett syndrome (RS) is a severe neurodevelopmental disorder that contributes significantly to severe intellectual disability in females worldwide. It is caused by mutations in MECP2 in the majority of cases, but a proportion of atypical cases may result from mutations in CDKL5, particularly the early onset seizure variant. The relationship between MECP2 and CDKL5, and whether they cause RS through the same or different mechanisms is unknown, but is worthy of investigation. Mutations in MECP2 appear to give a growth disadvantage to both neuronal and lymphoblast cells, often resulting in skewing of X inactivation that may contribute to the large degree of phenotypic variation. MeCP2 was originally thought to be a global transcriptional repressor, but recent evidence suggests that it may have a role in regulating neuronal activity dependent expression of specific genes such as Hairy2a in Xenopus and Bdnf in mouse and rat.